The potential of robotic, high and latest technology equipment used in maintenance and inspection of building in Malaysia / Hilmi Awaludin - Awaludin, Hilmi (Faculty of Architecture, Planning and Surveying, 2013)
Building inspection and maintenance is one of the main works done in Building surveying arena. The works requires equipment to some certain areas that by using it will increase the success rates, making the work to be easier to be done and giving the maintenance teams a better work. The equipment nowadays has been improving in order to achieve certain requirements that are needed to done the works. In the characteristic of robotic, latest technology, high technology, technological equipment, the entire characteristic here do give advantages in doing the work in a better ways. However some of the company in the area of building inspection and maintenance company doesn’t really use the robotic equipment in Malaysian industry because of no further research have been done on it. This might be different with the country that have a high potential in robotic area such as the Japan, china and western countries. However, the technological equipment does have some place with the Malaysian industries. The companies that have a direct relation with the work do use equipment that has the technological mechanism. This is mostly because the equipment does give a better result for the work. This study also identifies and finds the problem regarding the equipment’s or the tools and also brings the ways to overcome it. The findings give a clear view that it is better to change from the old equipment to a new one that do has a latest technology in it The increasing of the client, the better work result, the faster the works done is some types of the result when some specific body change to a latest technology. As the methodology, this research uses the interview and also the questionnaire method. The technological equipment does have the place in the industry of building service because of the increases of the building care mind amongst the people nowadays.